The Effect of Inflation and Unemployment on GDP: Evidence from Bangladesh - Bhawmick, Sojib; Akter, Shamima; Haque, Fazlul (South Asian Journal of Social Sciences and Humanities, 2023)
This study aims to investigate the impact of inflation and unemployment on GDP in Bangladesh from 1991 to 2021. The study utilizes unit root tests, the Autoregressive Distributed Lag (ARDL) Bound test, and the Error Correction Model (ECM) to analyze the relationships between these variables. The results indicate that GDP and inflation are stationary at both the level and first difference, while unemployment is stationary at the first difference and at the same time all three variables are stationary at the first difference. The ARDL Bound test reveals that both inflation and unemployment are harmful to GDP, hindering its growth over time. The F-statistics indicate a consistent relationship between the variables. The Error Correction Model shows a high correlation between the variables in both the short- and long-term, accounting for 82% of the equilibrium deviation. The findings suggest that policymakers should pay attention to the levels of inflation and unemployment in the country, as they have a significant impact on GDP growth.
Keywords: GDP; Inflation; Unemployment; Augmented Dicky-Fuller; Bangladesh